Evaluation of the GENE-UP®Cronobacter Method for the Detection of Cronobacter Species in Select Foods and Environmental Surfaces: Collaborative Study, First Action 2019.01. (29th January 2020) - Johnson, Ronald; Mills, John; Pittet, Jean-Louis; Rannou, Maryse; Bird, Patrick; Nelson, Maria
Abstract: Background: The GENE-UP ® Cronobacter assay ( Performance Tested Method SM 081801) is a real-time PCR technology for the rapid detection of Cronobacter species in select foods and environmental surfaces. Objective: The purpose of this validation was to evaluate the method's interlaboratory performance and submit the result to AOAC INTERNATIONAL for adoption as a First Action Official Method SM for the detection of Cronobacter species in select foods and environmental surfaces. Method: The GENE-UP method was evaluated in a multilaboratory study as part of the AFNOR NF VALIDATION certification process (NF102) following ISO 16140-2:2016 using unpaired test portions for one food matrix, reconstituted infant formula containing probiotics. The candidate method was compared to the ISO 22964:2017 reference method. Sixteen participants from fifteen laboratories throughout the European Union participated. Three levels of contamination were evaluated: a noninoculated control level (0 CFU/target test portion), a low contamination level (approximately 2 CFU/target test portion), and a high contamination level (approximately 10 CFU/target test portion). Data from that study were analyzed according to the probability of detection (POD) statistical model as presented in the AOAC validation guidelines. The difference in laboratory POD (dLPODC ) values with 95% confidence intervals across collaborators was calculated for each level between the candidate and reference method results and between the candidate presumptive and confirmed results. Results: The dLPODC values with 95% confidence intervals were 0.00 (–0.03, 0.03), –0.08 (–0.19, 0.02), and 0.00 (–0.03, 0.03) for the noninoculated, low, and high contamination levels, respectively. Conclusions: The dLPODC results indicate no significant difference between the candidate method and the reference method or between presumptive and confirmed results for all three levels of contamination. Highlights: The GENE-UP Cronobacter assay provides industry with a rapid, easy to use method for the rapid detection of Cronobacter in a wide range of products and environmental samples.